Non-destructive testing of 3D printed specimens - Ng, Cheong Hong (Nanyang Technological University, 2018)
Additive Manufacturing or 3D printing is becoming the mainstream manufacturing technology to produce parts with complex structure to achieve highest strength-to-weight ratio. Many companies are developing proprietary 3D materials and offering them as alternative to the conventional materials. In this study, 4 specimens with different thickness were 3D printed with Markforged Onyx, a proprietary Nylon material reinforced with chopped carbon fibre. They were all tested with two main ultrasonic testing techniques: pulse-echo and through transmission. Ultrasonic signal reflection was detected when testing the specimens however the signals were more complex compared to the reference metal material hence the detailed studies were also done on the signal with the change in thickness in order to assess the material properties in qualitatively manner. This study attempts to establish the basic ultrasonic testing parameters and analysis method for Markforged Onxy and this is believed to be the first non-destructive testing study on this proprietary material.